Estimation of Run Up and Arrival Time of Tsunami in Bali Region Based on TOAST Simulation - Purnama, Anak Agung Diah Satria; Alit Paramarta, I.B.; Rahman, Muh. Soekarno Saputra (BULETIN FISIKA, 2019)
Bali Island is an area that is flanked by two zones of earthquake potential to cause a tsunami. In this study produced the estimated tsunami heights (run up) and the tsunami arrival times (ETA) by simulating a tsunami with some magnitude variety of the earthquake using software called TOAST. The estimation is obtained by making a scenario of earthquake from parameters of earthquakes that have occurred and raised tsunami on the Bali Island as a reference. The observation area is in some coastal areas of Bali Island. The maximum value of run up is between 21.16 m to 55.6 m with tsunami arrival time is between 120 minutes to less than 15 minutes after an earthquake with 9.6 SR of magnitude . The area around Kuta Beach Badung is an area with high potential for run up.